Diagnosis of Inflammatory Bowel Disease by Abdominal Ultrasound and Color Doppler Techniques - Ahmed, Rehab; Debian, Hossam; Fawzi, Mohamed; Elsergany, Heba F.; Soliman, Moataz Yousry; Mohmed, Ahmed A. H.; Kandil, Alaa; Elmaghraby, Mostafa Bedair; Abd-Elsalam, Sherief; Abo-Amer, Yousry Esam-Eldin (Current Medical Imaging, 2021)
Background & Aims: The utility of ultrasound and color Doppler in the diagnosis and evaluation of inflammatory bowel diseases (IBD) has not been studied enough. Therefore, the aim of the current study was to evaluate the importance of conventional abdominal ultrasound and color Doppler in diagnosing IBD and assessing disease activity. Methods: The study was conducted at the National Hepatology and Tropical Medicine Research Institute (NHTMRI) between July 2018 and January 2019, in which 150 patients were suffering from diarrhea, dysentery, tenesmus, or rectal bleeding were evaluated by colonoscopy, high-resolution ultrasound, and color Doppler scans. Results: The present study was conducted on 150 patients; 84 (56%) had ulcerative colitis (UC), 16 (10.7%) had Crohn's disease (CD), and 50 (33.3%) had normal colonoscopy results with a mean age 37.2 ± 9.059. The superior mesenteric Artery Peak Systolic Velocity (SMA-PSV) and End Diastolic Velocity (EDV) were significantly higher in both UC and CD than in the control group; however, pulsatility index (PI) was significantly higher in the control group than both UC and CD. However, there was no significant difference between UC and CD. The inferior mesenteric artery PSV and EDV were significantly higher in both UC and CD than in the control group. Conclusion: Doppler ultrasound findings of SMA and IMA correlate with the incidence of inflammatory bowel disease, the site of disease, and its activity.
Keywords: Inflammatory bowel diseases